Analisis Pemeriksaan USG Thorax Marker dengan Klinis Efusi Pleura di Rumah Sakit Hermina Depok - Abdul Aziz, Sahal Fahmi; Apriantoro, Nursama Heru; Kuswoyo, Heri (Jurnal Imejing Diagnostik (JImeD), 2024)
Background: Pleural effusion is a hoarding fluid excess contained in the pleural cavity due to the formation and production of pleural fluid which is not balanced in condition. In this matter, Thoracic Ultrasound is a highly sensitive and specific imaging modality in evaluating the lungs for any various disorders, such as pneumonia, pleural effusion, pulmonary edema, and pneumothorax. The objective of this research: this research analyzes the management of Thorax Marker Ultrasound examination with clinical pleural effusion undertaken at Hermina Hospital Depok.Methods: As for the research design used, it apples qualitative descriptive method. Data collection techniques in this study used observation worksheets, interview sheets for Radiologists and Sonographers, and documentation tools.Results: The results showed technique of examination and results of description from Thorax Marker Ultrasound with clinical pleural effusion undertaken at Hermina Hospital Depok.Conclusions: . In conclusion, this research can be concluded that technique of Thorax Marker Ultrasound examination with clinical pleural effusion executed at Hermina Hospital Depok use transducer convex which is done longitudinally in the right intercostal area (between diaphragm and liver) or left intercostal (between diaphragm and spleen) in the mid axillary line, a little posterior to the plane coronal in accordance with the Radiography Thoracic description from the patient. Thorax Marker Ultrasound results with clinical pleural effusion executed in 3 samples, have 3 different characteristics namely maximal pleural effusion, septated pleural effusion, and minimal pleural effusion.Â